Methods for microbial DNA extraction from soil for PCR amplification - Yeates, C (Biological Procedures Online, 1998)
Amplification of DNA from soil is often inhibited by co-purified contaminants. A rapid, inexpensive, large-scale DNA extraction method involving minimal purification has been developed that is applicable to various soil types (1). DNA is also suitable for PCR amplification using various DNA targets. DNA was extracted from 100g of soil using direct lysis with glass beads and SDS followed by potassium acetate precipitation, polyethylene glycol precipitation, phenol extraction and isopropanol precipitation. This method was compared to other DNA extraction methods with regard to DNA purity and size.